Evaluation and identification of high yielding trees in Nigerian cocoa germplasm - Apshara, S. Elain; Bhat, V.R.; Ananda, K.S.; Nair, R.V.; Suma, D. (Journal of Plantation Crops, 2009)
Forty four Nigerian cocoa clones which are being conserved in the field gene banks of Central Plantation Crops Research Institute, Regional Station, Vittal, Karnataka were assessed for their growth and yield performance. Six year old trees were observed for their morphological characters and annual pod yields were compiled over eight years from five to twelve years of age after planting. Pod and bean characteristics were also studied for all the clones. Precocious, potential high yielders were identified from their vigorous growth habit in the introduced environment with sturdy stems and optimal canopy spread. Among the clones, NC-37, NC-23, NC-26, NC-50, NC-20, NC-51, NC-27 and NC-25 were identified as heavy bearers with an average of 61.9, 53.3, 49.4, 48.4, 45.1, 44.2, 43.9 and 43.0 pods per tree per year respectively and with high dry bean yields of more than one kilogram per tree per year. These clones recorded single bean weight of more than 1 gram, 10-15 per cent shelling percentage and more than 50 percent fat which made them suitable for industries as well.